2021
DOI: 10.3390/molecules26133969
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Addition of Nuts on the Thermal and Rheological Properties of Wheat Flour

Abstract: The aim of the study was to assess the influence of replacing wheat flour with hazelnuts or walnuts, in various amounts, on the thermal and rheological properties of the obtained systems. The research material were systems in which wheat flour was replaced with ground hazelnuts (H) or walnuts (W) in the amount of 5%, 10%, and 15%. The parameters of the thermodynamic gelatinization characteristics were determined by the differential scanning calorimetry method. In addition, the pasting characteristics were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 24 publications
7
17
1
Order By: Relevance
“…A similar trend has been shown in previous studies [22] analyzing the viscoelastic properties of gruels based on wheat flour systems with hazelnuts or walnuts. In the presence of water, gluten forms a three-dimensional net that provides the springy nature of the dough.…”
Section: Sweep Frequency Testsupporting
confidence: 89%
See 4 more Smart Citations
“…A similar trend has been shown in previous studies [22] analyzing the viscoelastic properties of gruels based on wheat flour systems with hazelnuts or walnuts. In the presence of water, gluten forms a three-dimensional net that provides the springy nature of the dough.…”
Section: Sweep Frequency Testsupporting
confidence: 89%
“…The values of tan δ indicate that the tested doughs have the character of weak structures, while the presence of nuts in the system intensified this tendency, which is stronger the greater the share of nuts in the system. Earlier studies by Pycia and Juszczak [22] also showed that the gels of the wheat flour-nut systems were weak gels.…”
Section: Sweep Frequency Testmentioning
confidence: 89%
See 3 more Smart Citations